PENGARUH KONSENTRASI NUTRISI HIDROPONIK DFT TERHADAP PERTUMBUHAN SAYURAN SAWI - Endang Sri Wahyuni (JURNAL BIOSHELL, 2017)
A study aimed at obtaining the right concentration of nutrient solution for the growth of mustard varieties with DFT hydroponics system has been implemented from December 2016 to February 2017 at Greenhouse of Faculty of Agriculture, Islamic University of Jember.The research method used is factorial, consisting of 2 factors namely factor I is the concentration of nutrient solution consisting of 3 levels those are N1: 1000 ppm, N2: 1200 ppm and N3: 1400 ppm and factor II is varieties of mustard consisting of 3 levels namely, V1: Pagoda (Brassica rapa Japanese Group), V2: Green (Brassica rapaParachinensis Group), and V3: Pakcoy (Brassica rapa Chinensis Group).The data were analyzed by Analysis of Variance (Anova) with post hoc test Duncan 5%.The results showed that the concentration of 1,400 ppm gave the best growth effect to all tested varieties of mustard, but not significantly different compare to concentration of 1.200 ppm on Green variety. Keywords: mustard varieties, DFT hydroponics, nutrient consentration.